The relationship between knee function and psychology on sports readiness, overuse conditions, and physical activity post anterior aruciate ligament reconstructions: a literature review - Vinzenza Bondeng; I Putu Gde Surya Adhitya; Sayu Aryantari Putri Thanaya (PT. Kesehatan Gerak Fungsi Tubuh, 2023)
Background : Anterior cruciate ligament (ACL) injuries are injuries that result from a tear in the ligament that connects the femur and tibia. This injury can be treated with anterior cruciate ligament reconstruction (ACLR), which is an operation in the form of replacing the ACL ligament with other tissue grafts. ACLR can affect knee function so that it has an impact on readiness to return to sports, physical activity levels and the emergence of overuse conditions. Objective : To determine the relationship between knee function and psychology on readiness to return to sports, overuse conditions, and physical activity after Anterior Cruciate Ligament Reconstructions. Method : The method used is a literature review study using secondary data from published literature. The literature search was conducted online through PubMed, Pedro, Garuda and Google Scholar, using the “key words” Anterior cruciate ligament reconstructions (ACLR), ACL injury, psychological factors, physical activity of ACL athletes, and overuse injuries and selected based on inclusion and exclusion criteria. Results : From the literature used, it is stated that poor knee function can cause severe pain and fear of re-injury so that it has an impact on readiness to return to sports and decreased levels of physical activity after ACLR. Poor knee function due to surgical factors such as the ipsilateral ACL autograft surgical technique can result in an overuse condition characterized by the emergence of patellofemoral pain syndrome. Conclusion : There is a relationship between knee function on psychological readiness to return to sports, level of physical activity and overuse conditions in athletes after ACL reconstruction. Keywords : ACL Reconstruction, Psychological Readiness and Physical Activity of ACLR Athletes.